Strategic Human Resources Management And Organisational Resillience In Indonesian Start-Ups - Permana, Dudi; Rustiawan, Indra; Sya'rani, Ridwan (Indonesian Scientific Publication, 2024)
In Indonesian retail enterprises, this study explores the complex links between HR practices, employee empowerment, workforce diversity, organizational communication, organizational resilience, and employee retention. Utilizing Structural Equation Modeling with Partial Least Squares (SEM-PLS), a quantitative methodology was utilized to examine data gathered from 215 workers in a range of roles in the retail industry. Organizational communication and employee retention, workforce diversity and organizational resilience, and employee empowerment and retention were all found to have strong beneficial correlations with HR practices. Furthermore, corporate communication, diversity in the workforce, employee empowerment, and HR policies all had a substantial positive impact on employee retention and organizational resilience. The suggested model's validity was reinforced by the model fit indices, which attested to its sufficiency. These results highlight the holistic integration of these aspects to promote resilience and retention in the dynamic Indonesian retail sector, offering insightful information to HR practitioners and organizational leaders. The findings of this study provide real implications for leaders in the manufacturing industry in Indonesia in maintaining organizational resilience.